Thermal analysis of fractures at Cerberus Fossae, Mars: Detection of air convection in the porous debris apron - Antoine, R.; Lopez, T.; Baratoux, D.; Rabinowicz, M.; Kurita, K. (Icarus (New York, N.Y. 1962), 2011)
► Analysis of thermal data of the surface of Mars. ► Role of gas circulation in the ground in controlling surface temperature. ► Thermal anomalies at Cerberus Fossae, Mars. This study investigates the cause of high nighttime temperatures within Cerberus Fossae, a system of fractures affecting the Central Elysium Planitia. The inner parts (walls and floor) of the fractures are up to 40 K warmer than the surrounding plains. However, several temperature profiles exhibit a local temperature minima occurring in the central part of the fractures. We examined first the influence of cooling efficiency at night in the case of a strong reduction of the sky proportion induced by the fracture’s geometry. However, the lack of correlation between temperature and sky proportion, calculated from extracted Mars Orbiter Laser Altimeter (MOLA) profiles argues against this hypothesis. Albedo variations were considered but appear to be limited within the fractures, and are generally not correlated with the temperatures. Variations of the thermal properties of bedrocks exposures, debris aprons and sand dunes inferred from high-resolution images do not either correlate with temperature variations within the fractures. As none of these factors taken alone, or combined, can satisfactorily explain the temperature variations within and near the fracture, we suggest that geothermal heat transported by air convection within the porous debris aprons may contribute to explain high temperatures at night and the local minima on the fracture floor. The conditions for the occurrence of the suggested phenomenon and the consequences on the surface temperature are numerically explored. A conservative geothermal gradient of 20 mW/m 2 was used in the simulations, this value being consistent with either inferred lithosphere elastic thicknesses below the shield volcanoes of the Tharsis dome or values predicted from numerical simulations of the thermal evolution of Mars. The model results indicate that temperature differences of 10–20 K between the central and upper parts of the fracture are explained in the case of high Darcy velocities which require high permeability values (5 × 10 −6 m 2). The presence of coarse material composing the debris aprons may explain why this key criteria was met in the context of Cerberus Fossae.